Attack Stream Cipher By Using Cipher System Only - Hussein, K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Attack stream cipher system , using cipher text only , depends on the characteristics of plain teKt language and the randomness of the key , that used in encryption , without having detailed k.nuwh:dgt:: uf cipher algorithm by benefiting from the balance between O’s and I’ in the key to reduce the probability of key space.